(untitled) (INTERNATIONAL CONFERENCE ON ADVANCE SCIENCE AND TECHNOLOGY, 2024)
The article describes the analysis of theoretical and practical views on the specific aspects of educational activities during adolescence. Also, researches of foreign scientists on educational motivation in adolescence are described. Empirical issues of the formation of learning motivation during adolescence have been explained.